Examining Reasons for Using Non‐Primary Care Providers as Usual Source of Health Care: Insights From the All of Us Study - Abbey Gregg; Hui Wang; Brankeciara Ard; Marcelo Takejame Galafassi; Maryam Bidgoli (Health Care Science)
ABSTRACT Introduction Having a primary care usual source of care (USC) is associated with better population health outcomes. However, the percent of adults in the United States (US) with a usual primary care provider is declining. We sought to identify factors associated with establishing a USC at an urgent care clinic or emergency department as opposed to primary care. Methods We analyzed data from 57,152 participants in the All of Us study who reported having a USC. We used the Andersen Behavioral Model of Health Services Use framework and multivariable logistic regression to examine associations among predisposing, enabling, and need factors, according to the source of usual care. Results An urgent care clinic, minute clinic, or emergency department was the source of usual care for 6.3% of our sample. The odds of seeking care at this type of facility increased with younger age, lower educational attainment, and better health status. Black and Hispanic individuals, as well as those who reported experiencing discrimination in medical settings or that their provider was of a different race and ethnicity, were also less likely to have a primary care USC. Financial concerns, being anxious about seeing a provider, and the inability to take time off from work also increased the likelihood of having a non‐primary care USC. Conclusions Improving the rates of having a primary care USC among younger and healthy adults may be achievable through policies that can improve access to convenient, affordable primary care. Efforts to improve diversity among primary care providers and reduce discrimination experienced by patients may also improve the USC rates for racial and ethnic minority groups.